CCR5-Positive Inflammatory Monocytes are Crucial for Control of Sepsis. Issue 5 (November 2019) - Castanheira, Fernanda Vargas e Silva; de Lima, Kalil Alves; Cebinelli, Guilherme Cesar Martelossi; Sônego, Fabiane; Kanashiro, Alexandre; Colon, David-Fernando; Borges, Vanessa; Czaikoski, Paula Giselle; Mota, José Mauricio; Cunha, Thiago Mattar; Alves-Filho, José Carlos; Liew, Foo Y.; et al.
Abstract : ABSTRACT: Neutrophils and inflammatory monocytes control sepsis by migration to the site of infection via their chemokine receptors. CCR5 is a chemokine receptor that is not expressed on neutrophils and inflammatory monocytes under homeostatic conditions. However, it has been demonstrated that CCR5 can become expressed on these cells during different models of inflammation. In the present study, we investigated if CCR5 is also expressed on neutrophil and inflammatory monocytes during sepsis, exerting an important role in the migration of these cells to the infectious focus. Using cecal ligation and puncture model to induce polymicrobial sepsis, we demonstrated that the expression of CCR5 is induced on CD11b + Ly6G − Ly6C high inflammatory monocytes, but not on neutrophils (CD11b + Ly6G + Ly6C − ). Furthermore, CCR5 plays an important role for the migration of the inflammatory monocytes to infection focus during sepsis. CCR5-expressing inflammatory monocytes migrate from the bone marrow to the circulation and then into the site of infection, where they phagocytize and kill the bacteria. Consequently, CCR5 −/− mice showed increased systemic inflammatory response and mortality compared to wild-type mice. These data therefore demonstrate a hitherto unrecognized protective role of CCR5 in sepsis. Abstract : Supplemental Digital Content is available in the text